The Dynamical Behavior of Boundary Layer Ozone in Winter - Shi, Xiaoqin (ProQuest Dissertations & Theses, 2023)
The work focuses on the ozone behavior in the winter boundary layer in the urban area of Beijing. The budget of boundary layer ozone is subject not only to chemical reactions in the atmosphere, but also to turbulent mixing in the boundary layer, advective transport of air masses, pollutant emissions, etc. The dissertation investigates three main external forcing factors of the boundary layer ozone budget in the urban area of Beijing in winter. Two forcing factors affecting the development of turbulence in the boundary layer are large-scale wind and urban heat. Anthropogenic emission related to ozone production and depletion is the third forcing factor. Numerical simulations using the chemical transport model WRF-Chem are performed to investigate the ozone responses to the three external forcing factors. First, under the control of winter monsoon in the Beijing region, a strong northerly wind frequently invades the region and enhances the ozone level in the urban area by up to two times. Four simulations with different nudging strategies are performed to simulate different wind representations. By comparing four nudging simulations, the ozone enhancement in the urban area during the invasion of strong northerly wind is explained by ozone advection from the mountainous areas and the enhanced mechanical turbulent mixing. Good representation of wind shear during the strong northerly wind invasions is essential for reproducing ozone enhancement. Secondly, the important role of urban heat in the evolution of ozone during the day-to-night transition is highlighted. The lowest value of the eddy diffusivity K is reached during the day-to-night transition in simulations without urban heat effect, accompanied by a rapid accumulation of nitrogen oxides (NO x=NO+NO 2) and the associated rapid depletion of ozone. But in the simulation with urban heat effect, the increased turbulent mixing of ozone and NO x leads to significant bias reductions of ozone, from -68% to +0.7%, and of NO2, from +75% to +6%. Thirdly, the responses of ozone to anthropogenic emissions are tested by redistributing emissions vertically (vertical injection), temporally (diurnal/weekly variation) and horizontally (downscaling). It is found that the simulated ozone concentrations respond strongly to the emission changes in the nocturnal boundary layer due to its low diffusion capacity. The long-narrow zone along the foothills southwest of Beijing is also more sensitive to changes of emissions (in this case the downscaled emissions) than other regions because the southerly wind directed towards the western mountains results in low diffusion capacity. Finally, special attention is paid to the ozone responses to the vast emission reductions following the outbreak of COVID-19 pandemic in China in the first two months of 2020. Contrasting responses of ozone to the nation-wide emission reductions are observed and simulated. In Northern China, the most polluted area in winter, observations show that ozone level increases by a factor of 2 (±0.7) associated with a 53% (±10%) reduction in NO 2, while ozone levels in rural areas of Southern China decrease slightly. The different chemical regimes of ozone production explain the contrasting responses of ozone to NOx emission reductions during the pandemic. The studies in this dissertation show a novel perspective in studying ozone behavior and provide insights into ozone behavior in the polluted winter boundary layer in light of the increasing ozone trend in China.